Enhancing Mandibular Reconstruction with Surgeon–Bioengineer Collaboration: A Protocol for Virtual Surgical Planning - Dong-Ho Shin; Hyo-Joon Kim; Ji-Su Oh; Seong-Yong Moon (Applied Sciences)
Background/Objectives: Computer-assisted mandibular reconstruction requires sophisticated technical expertise alongside surgical knowledge. This study aims to establish and validate an efficient collaborative protocol between oral and maxillofacial surgeons and bioengineers for virtual surgical planning in mandibular reconstruction. Methods: We developed a structured protocol with four sequential phases: (1) generation of 3D models from CT data, (2) virtual resection planning, (3) reconstruction design, and (4) surgical guide fabrication. Protocol efficiency was assessed through seven simulation trials measuring planning duration and required revisions. Clinical validation was performed in four mandibular reconstruction cases. Accuracy was evaluated by comparing virtual surgical plans to postoperative outcomes using 3-matic 13.0 software analysis. Results: Protocol implementation showed consistent efficiency across simulations with a mean planning duration of 2.86 working days (SD = 1.35). Only two of seven simulations required design revisions. Clinical application in four cases (three ameloblastomas, one odontogenic myxoma) demonstrated high precision with a mean virtual-to-actual discrepancy of 0.90 mm (SD = 0.34). Successful reconstructions were achieved across varying defect spans (29–53 mm) using both bicortical deep circumflex iliac artery (DCIA) flaps and monocortical iliac block bone grafts. The collaborative workflow resulted in optimized surgical guide design, reduced planning iterations, and improved surgical precision. Conclusions: The established surgeon–bioengineer collaborative protocol enhances the efficiency and accuracy of computer-assisted mandibular reconstruction while making advanced surgical planning techniques more accessible. While initial results are promising, future studies with larger patient cohorts and extended follow-up periods are needed to fully validate the protocol’s long-term benefits and broader applicability.